Effect of Probiotic on Microflora Population and Carcass Yield of Quail, Coturnix japonica - Norshida, Ismail; Ahmad Syazni, Kamarudin; Aliyu Garba, Khaleel (2019)
This study was conducted to determine the effect of dietary probiotic on intestinal and fecal microflora and carcass yield of broiler quails during the four weeks of feeding period. The quails were fed a basic diet (group 1) which acted as the control group; another 3 groups were fed basal diet with probiotic added at concentrations of 0.05%, 0.20% and 0.35% respectively for 28 days after two weeks of brooding. On day 42, fecal sample and intestinal sample were collected for microbial analysis and carcass yield of the quails was evaluated by cutting the selected parts of the carcass. The results showed that there was a significant difference (p 0.05) in Escherichia coli population in quail’s intestine between control and treatment group, but significantly (p < 0.05) different in Lactobacillus population. Different inclusion rate of probiotic including control showed negative result of Salmonella in both intestine and feces of quail. In addition, supplementation of the diet with probiotic resulted in higher dressing and legs percentage of the carcass but do not affect the breast percentage. This shows that adding probiotic to the broiler quail’s diet can improve the performance of the quails by increasing the beneficial microflora and reducing the pathogenic microorganisms, and relatively higher carcass yields.